A Prospective Observational Study of Drug Therapy Problems in Pediatric Ward of a Referral Hospital, Northeastern Ethiopia. (21st March 2020) - Bizuneh, Gizachew Kassahun; Adamu, Betelhem Anteneh; Bizuayehu, Getenet Tadege; Adane, Solomon Debebe
Abstract : Background . A drug therapy problem is any undesirable event experienced by a patient during drug therapy that interferes with achieving the desired goals of therapy. It has been pointed out that hospitalized pediatric patients are particularly prone to drug-related problems. Identifying drug therapy problems enables risk quantification and determination of the potential impact of prevention strategies. The purpose of this study was to assess the drug therapy problems in a pediatric ward of Dessie Referral Hospital, northeast of Ethiopia, and to identify associated factors for drug therapy problems. Methods . A prospective observational study design was carried out to assess drug therapy problems in a pediatric ward of Dessie Referral Hospital from February 1, 2018, to May 30, 2018. Ethical approval was obtained, and informed consent was signed by each study participant's parent before the commencement of the study. All patients admitted to the ward during the study period were included in the study. Data was collected by trained pharmacy staffs through medical record reviews of patients using a prepared standard checklist and semistructured questionnaire. The collected data were cleared and checked every day for completeness and consistency before processing. Data were entered, and descriptive statistical analysis was done using SPSS Version 20 Software. A P value of less than 0.05 was considered significant. Results . The participants' mean age was 2.32 years with the standard deviation (SD) of 0.76 years. Among 81 patients, 71 (87.7%) of them had at least one drug therapy problem per patient which indicates that the prevalence of the drug therapy problem was substantially high. Needs additional drug was the most predominantly encountered drug therapy problem accounted (30 (25.2%)). On the other hand, ineffective drug was the least (3 (2.5%)) drug therapy problem. Antibiotics (47 (39.5%)) followed by fluid and electrolyte (25 (21%)) were classes of drugs mostly involved in the drug therapy problem. The main risk factors reported to the occurrence of the drug therapy problems were prescribing and dose calculation errors. Conclusion . The present study revealed that majority of the patients had at least one DTP per patient; this indicates that prevalence of DTP was very high in the study area. Needs additional drug therapy followed by noncompliance was the major cause of the occurrence of DTP. Antibiotics were the main class of drugs involved in the drug therapy problem, and among the risk factors assessed, prescribing and dose calculation errors showed statistical significance.